Considering the attitude of common law system on principle of good faith: with emphasis on its overview in the CISG / Yaser Farmani ... [et al.] - Farmani, Yaser; Zahid, Anowar; Moghadamfard, Mohammad; Shahmohamadi, Mohamad Naji (2014)
Good faith is raised as a significant issue in the common law system. It is visible in many statute documents in common law countries as well as many international treaties in which common law countries are signatories. However, the problem still exists. In common law this principle is not generally accepted as a governing rule in contracts, but it can be said that in special cases, like consumer law and insurance law it plays a main role. The reason for this view in common law maybe due to the traditional view point on the originality of the contract and avoiding a legal principle with high power that can make changes in the contract. However, a modern view point in common law is beginning to emerge, which highly recommends strengthening good faith in the contract.